Effects of renal denervation therapy on cardiac function and malignant arrhythmia in patients with reduced left ventricular ejection fraction and narrow QRS complexes treated with implantable cardioverter defibrillator - Yang, Wei; Xu, You-Long; Gao, Jun-Qing; Shen, Deng; Li, Min; Fa, Jing-Jing; Zhang, Ying; Wang, Rui; Hou, Shu-Xin; Hu, Wen-Ying; Jin, Hui-Gen; Liu, Zong-Jun (Frontiers in Physiology, 2022)
Objective: The purpose of this study was to explore the effects of renal denervation (RDN) on cardiac function and malignant arrhythmia in patients with reduced left ventricular ejection fraction (HFrEF) and narrow QRS treated with implantable cardioverter defibrillator (ICD). Methods: A total of 20 eligible HFrEF patients [left ventricular ejection fraction (LVEF)<40%] and narrow QRS complexes (QRS duration<120ms) were randomized into either the ICD plus RDN group or the ICD only group during April 17, 2014 to November 22, 2016. Clinical data including clinical characteristics, blood biochemistry assessment, B-type natriuretic peptide (BNP), echocardiographic indexes, 6-minute walking distance (6MWD), New York Heart Association (NYHA) classification and count of ICD discharge event before and after operation were analyzed. Patients were followed up to 3 years post ICD or ICD plus RDN. Results: Baseline clinical data were comparable between the two groups. Higher LVEF (%) (Mixed model repeated measure, P=0.0306) (39.50±9.63% vs. 31.20±4.52% at one year; 41.57±9.62% vs. 31.40±8.14% at three years), systolic blood pressure (P=0.0356), and longer 6MWD (p<0.0001) as well as reduction of NYHA classification (p<0.0001) were evidenced in ICD plus RDN group as compared to ICD only group during follow up. Patients in ICD plus RDN group experienced less ICD discharge events (2 vs. 40) and decreased diuretic use; rehospitalization rate (30% vs.100%, P=0.0031) and cardiogenic mortality rate (0 vs. 50%, P=0.0325) were also significantly lower in ICD plus RDN group than in ICD only group during follow up. Conclusion: ICD implantation plus RDN could significantly improve cardiac function and cardiac outcome as well as increase exercise capacity as compared to ICD only for HFrEF patients with narrow QRS complexes.